Differences in human papillomavirus type distribution in high‐grade cervical intraepithelial neoplasia and invasive cervical cancer in Europe1. Issue 4 (24th July 2012) - Tjalma, Wiebren A.; Fiander, Alison; Reich, Olaf; Powell, Ned; Nowakowski, Andrzej M.; Kirschner, Benny; Koiss, Robert; O'Leary, John; Joura, Elmar A.; Rosenlund, Mats; Colau, Brigitte; Schledermann, Doris; et al.
Abstract Knowledge of differences in human papillomavirus (HPV)‐type prevalence between high‐grade cervical intraepithelial neoplasia (HG‐CIN) and invasive cervical cancer (ICC) is crucial for understanding the natural history of HPV‐infected cervical lesions and the potential impact of HPV vaccination on cervical cancer prevention. More than 6, 000 women diagnosed with HG‐CIN or ICC from 17 European countries were enrolled in two parallel cross‐sectional studies (108288/108290). Centralised histopathology review and standardised HPV‐DNA typing were applied to formalin‐fixed paraffin‐embedded cervical specimens dated 2001–2008. The pooled prevalence of individual HPV types was estimated using meta‐analytic methods. A total of 3, 103 women were diagnosed with HG‐CIN and a total of 3, 162 with ICC (median ages: 34 and 49 years, respectively), of which 98.5 and 91.8% were HPV‐positive, respectively. The most common HPV types in women with HG‐CIN were HPV16/33/31 (59.9/10.5/9.0%) and in ICC were HPV16/18/45 (63.3/15.2/5.3%). In squamous cell carcinomas, HPV16/18/33 were most frequent (66.2/10.8/5.3%), and in adenocarcinomas, HPV16/18/45 (54.2/40.4/8.3%). The prevalence of HPV16/18/45 was 1.1/3.5/2.5 times higher in ICC than in HG‐CIN. The difference in age at diagnosis between CIN3 and squamous cervical cancer for HPV18 (9 years) was significantly less compared to HPV31/33/'other' (23/20/17 years), and for HPV45 (1 year) than HPV16/31/33/'other' (15/23/20/17 years). In Europe, HPV16 predominates in both HG‐CIN and ICC, whereas HPV18/45 are associated with a low median age of ICC. HPV18/45 are more frequent in ICC than HG‐CIN and associated with a high median age of HG‐CIN, with a narrow age interval between HG‐CIN and ICC detection. These findings support the need for primary prevention of HPV16/18/45‐related cervical lesions.